KHASIAT JAHE BAGI KESEHATAN TUBUH MANUSIA - Harwati, CH. Tri (Innofarm:Jurnal Inovasi Pertanian, 2009)
ABSTRACT Ginger ( Zingber officinale ), is a rhizome plant that is very popular as a spice and medicinal materials. Institut Pertanian Bogor ( IPB ), through its center for theÂ  studyÂ  of Biofarma conduct research that giger is very useful for health. According to Prof Ir Dr K Darusman Latifah, Head IPB Biofarma Studies Center, assisted by two of his staff, namely Rudi Heryanto, SSi, MSi (active ingredient separation expert) and Dr Min Rahminiwati (pharmacologists): ginger no harmful effects to be generated by the chemical components in ginger for its use conducted in accordance with the recommendation. Bioactive compounds contained in ginger (gingerol or atsiri oil ) is a thermo labile compound gingerol can survive until the temperature of 100 degrees Celsius. In a monograph, mentioned that the use of ginger powder orally at levels of 2 grams per day (in a single dose or divided into several times) can be done in the not-limited. The use of ginger powder at doses of 6 grams per day can cause stomach irritation. In preclinical both in vitro and in vivo, ginger has been shown to have effects Antimicrobial, antifungal, antihelmintic, antioxidant, antiimflamation, anticancer, imunomodulatory, antilipidemic, analgesic, and has a protective effect on the digestive tract. While in the clinical most obvious effect of ginger is to relieve symptoms of nausea in pregnant women. For other effects such as preventing nausea after surgery, preventing carsick, seasick, airsick and osteoarthritis, a clinical study until now is quite effective, ginger is believed to replace aspirin and similar drugs. Key Word : Ginger, spice, medicinal materials.